Exercise stereotypes and fatigue in people living with HIV: does self-efficacy play a mediating or a moderating role? - Laura Gray; Aïna Chalabaev; Jacques Durant; Eric Rosenthal; Christian Pradier; Martin Duracinsky; Isabelle Rouanet; Laura Schuft; Serge S. Colson; Fabienne d'Arripe-Longueville (BMC, 2018)
Abstract Background Recent research suggests that exercise stereotypes may influence physical activity through ego depletion and internalization mechanisms. The objective of this study was to better understand exercise stereotypes mechanisms among people living with HIV (PLHIV) by further examining the role of exercise self-efficacy and perceived physical fatigue in the relationship between exercise stereotypes and physical activity. Methods Three hundred five people living with HIV were recruited to provide data on their stereotypes related to exercise, exercise self-efficacy, perceived physical fatigue as well as their level of physical activity (PA). Results From the different models tested, the serial mediation model with exercise self-efficacy and perceived physical fatigue as mediators of the relationship between exercise stereotypes and PA, as well as the moderated mediation model with exercise selfefficacy as a moderator of exercise stereotypes and perceived physical fatigue a mediator, provided good fits to the data. However, the moderated mediation model (with indirect associations between negative exercise stereotypes and PA via perceived physical fatigue being moderated by exercise self-efficacy) explained the most variance in PA (R2 = .27). Conclusion The moderated mediation model suggests that exercise stereotypes might influence PA through ego depletion mechanisms and be tempered by exercise self-efficacy.